Regional sonology of the upper limb - II: Wrist and hand - Bipin R Shah; Ankit B Shah (Indian Journal of Rheumatology)
With the advent of musculoskeletal ultrasound (US), there has been a paradigm shift in the way rheumatological conditions are detected, quantified and managed. Small joints of the wrist and hand play an important role in the diagnosis and characterization of inflammatory arthritis. Successful scanning of the wrist and hand requires good scanning equipment, thorough knowledge of anatomy and scanning protocols. The dorsal recesses of the wrist, metacarpophalangeal joint, proximal interphalangeal joint and the distal interphalangeal joint are scanned to look for joint effusion, synovial hypertrophy and cortical erosions. The extensor tendons of the wrist and hand have a synovial sheath at the level of the distal radius. The flexor tendons and the median nerve along the volar aspect of the wrist pass through a fibro-osseous tunnel known as the carpal tunnel. US pathologies commonly encountered in inflammatory arthritis have been very well defined in literature, so that there is better reproducibility of the tests and reduction in the inter-observer variation.